Association of fitness and body fatness with left ventricular mass: The Heart Health Study - Renee J. Rogers; Erik B. Schelbert; Wei Lang; Yaron Fridman; Nalingna Yuan; John M. Jakicic (Wiley, 2020)
Summary Objective Left ventricular mass (LVM) is a clinical prognostic indicator of cardiovascular disease. Left ventricular mass is associated with body size (body mass index [BMI], weight, and body surface area [BSA]). This study examined if the association between body size (weight, BMI, and BSA) and LVM is influenced by body composition and cardiorespiratory fitness in adults who are overweight or obese. Methods This study included cross‐sectional baseline data from a randomized clinical trial. Participants included 379 adults (age, 45.6 ± 7.9 y) who were overweight or obese (BMI, 32.4 ± 3.8 kg·m−2). Measures included weight, height, BMI, BSA, body composition, cardiorespiratory fitness, and LVM by cardiac magnetic resonance imaging (CMR). Results Left ventricular mass was positively associated with weight, BMI, BSA, and fitness (P < .0001) and inversely associated with percent body fat (P < .0001). Stepwise multiple regression models showed that body fatness was inversely associated and cardiorespiratory fitness was positively associated with LVM even after considering weight, BMI, or BSA in the analyses. Conclusions These cross‐sectional findings support that in adults who are overweight or obese but otherwise relatively healthy, LVM is associated with both body composition and cardiorespiratory fitness. This may indicate the need to reduce body fatness and improve fitness for patients with obesity to enhance cardiovascular structure and function.